2023
DOI: 10.1371/journal.pone.0285369
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, characteristics, consequences, and awareness of work-related musculoskeletal pain among cardiac sonographers compared with other healthcare workers in Saudi Arabia: A cross sectional study

Abstract: Background Evidence related to work-related musculoskeletal pain (WRMSP) among cardiac sonographers is incomplete. This study aimed to investigate the prevalence, characteristics, consequences, and awareness of WRMSP among cardiac sonographers compared with other healthcare workers in different healthcare settings in Saudi Arabia. Methods This was a descriptive, cross-sectional, survey-based study. An electronic self-administered survey using a modified version of the Nordic questionnaire was distributed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 26 publications
3
3
0
1
Order By: Relevance
“…Our findings agree with those of previous domestic and global studies that demonstrated a high prevalence of WMSP among cardiac sonographers [ 2 , 7 , 8 , 11 ]. This high percentage of WMSP necessitates a holistic approach despite advanced developments in the design of ergonomic workstations with sophisticated equipment and ultrasound systems.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our findings agree with those of previous domestic and global studies that demonstrated a high prevalence of WMSP among cardiac sonographers [ 2 , 7 , 8 , 11 ]. This high percentage of WMSP necessitates a holistic approach despite advanced developments in the design of ergonomic workstations with sophisticated equipment and ultrasound systems.…”
Section: Discussionsupporting
confidence: 93%
“…This high percentage of WMSP necessitates a holistic approach despite advanced developments in the design of ergonomic workstations with sophisticated equipment and ultrasound systems. The pain locations revealed by cardiac sonographers in our study were consistent with those reported in our previous national study and in the literature [ 2 , 8 , 9 , 11 ]. Female sex is also a risk factor for WRMSP [ 23 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Son el resultado del desequilibrio entre las demandas biomecánicas y las capacidades funcionales del trabajador. 6 Los trastornos musculo esqueléticos se relacionan con la incapacidad laboral, dentro de los cuales se encuentra con mayor prevalencia la tendinitis del manguito rotador, bursitis, síndrome del túnel carpiano, tenosinovitis de Quervain, epicondilitis lateral y medial, dolor lumbar inespecífico, entre otros. 7 Estas lesiones en algunas ocasiones son de difícil diagnóstico ya que en la mayoría de los casos la única manifestación es el dolor que es una sensación subjetiva por lo que es necesario analizar las condiciones laborales a las que está expuesto trabajador.…”
Section: Introductionunclassified